Penilaian Dan Perhitungan Imbuhan Air Tanah Alami Pada Cekungan Air Tanah Umbulan - Heni Rengganis (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2011)
Indication of land use changes in Umbulan groundwater basin and its surroundings, was detected a few years ago. Floods occurred in recent years due to densely population urban areas and communities based onfarming in the hilly area on Tengger mountain slope. Related with the proposed utilization of Umbulan spring for clean water supply for some cities and districts in East Java, calculation was carried out to estimate the groundwater recharge. The calculation was done by using NAM rainfall runoff simulation model as part of the MIKE 11 model system. The calculation results of NAM simulation model process of some catchments of groundwater recharge rate within the Umbulan groundwater basin are: Rejoso catchment, 633 mm, Petung catchment, 568.7 mm, and Gembong catchment, 655.8 mm. All of the analysis results can be used in the calculation of water availability potency in a groundwater basin, and the final results then are used for input and proposal of groundwater management and development related to regional spatialplanning.